End member analysis of grain size distributions, sortable silt and geochemical data from a 2.68 m sediment core (GC-02) collected from the eastern Arabian Sea during 2010, over the past ⁓50,000 years - Ansari, Mohammad Arif (PANGAEA, 2025)
This dataset presents end member analysis of grain size distribution, sortable silt and geochemical data derived from a 2.68-meter-long sediment core (Core ID: GC-02), retrieved from the continental slope off Goa, eastern Arabian Sea (15.9947° N, 71.9994° E; water depth: 1850 m) during a sampling campaign in 2010. The core spans approximately the last 50,000 years (Late Quaternary), as determined by an age model based on accelerator mass spectrometry (AMS) radiocarbon dating and Bayesian age-depth modelling. The measurements were conducted at 1–2 cm resolution using a laser diffraction particle size analyzer. The dataset includes five end member loadings (EM1–EM5) extracted through End Member Analysis (EMA) using the AnalySize package in MATLAB and sortable silt. Major and trace element concentrations were determined to calculate elemental ratios such as La/Sc, Sc/Th, and Co/Th. These ratios are included in the dataset to support investigations of sediment provenance and source rock composition. The data were collected to document temporal variations in sediment texture and composition on centennial- to millennial-scale timescales in the eastern Arabian Sea. The dataset is intended to support further research on sediment transport processes, provenance discrimination, and Late Quaternary environmental reconstructions.
Keywords: Arabian Sea; end-member modelling; Monsoon; Solar radiation; sortable silt